Distinct gut microbiota of healthy children from two different geographic regions of Thailand - La-ongkham, Orawan; Nakphaichit, Massalin; Leelavatcharamas, Vichai; Keawsompong, Suttipun; Nitisinprasert, Sunee (Archives of microbiology, 2015)
In Thailand, food consumption by people from each region is different. This can be an important environmental factor which shapes the gut microbiota further affecting their health. This study aimed to use quantitative PCR (qPCR) to investigate the intestinal microbial community in 60 healthy children (aged 8–11 years) living in specific areas, namely central (CT) and northeastern (NE) Thailand where each region has its own typical food consumption. The children from NE had significantly higher consumption frequency of meat (chicken and beef), a wide variety of carbohydrate sources (noodle, fermented rice and sweet potato) including vegetables and fruit, while in CT, there was a significant preference for rice, breakfast cereal and cow milk. The qPCR analysis resulted in significantly higher abundance of lactobacilli, Clostridium coccoides–Eubacterium rectale, Clostridium leptum, Prevotella and Bacteroides fragilis in children from the NE region. However, no significant difference in the count of Bifidobacterium spp., Enterobacteriaceae and methanogens was observed. Considering the correlation of food sources and microbial groups, the consumption frequency of vegetables showed a moderately positive correlation coefficient of 0.42 and 0.34 to the Lactobacillus group (P = 0.001) and the Prevotella group (P = 0.008), respectively, while a diet of fish and beef showed a moderately negative correlation coefficient of −0.41 (P = 0.001) and −0.33 (P = 0.09) to Bifidobacterium spp., respectively. Our results suggested that high frequency consumption of varieties of carbohydrates, protein sources, fruits and vegetables by the NE children promoted a high abundance of bacterial species in the phyla Firmicutes and Bacteroidetes.